Contested Waters: An Environmental History of the Colorado River - April R. Summitt (University Press of Colorado, 2013)
Standing astride the Colorado River is a mass of concrete stretching 660 feet across the deep, sandstone canyon and reaching up its steep walls to a height of more than 726 feet. When it was completed in 1936, the Hoover Dam was the largest concrete structure ever built. Costing $49 million and 112 human lives, this massive triumph of human engineering still inspires awe in the nearly 1 million visitors who view it every year. It symbolizes the human ability to control nature, to harness a river. Its seventeen giant turbines turn the river’s power into 4.2 billion kilowatt-hours of electricity each year for California, Nevada, and Arizona. Below Hoover Dam, the Colorado flows at a gentle pace for almost 300 miles before it is almost completely halted at Morelos Dam. Once the river reaches that point just across the Mexico border, its flow is diverted at a right angle to the west to irrigate Mexicali farms. Only a small trickle makes it through the dam to the delta, reaching the sea on rare occasions. Partially sustained by salty agricultural runoff, the Ciénega de Santa Clara wetlands provide vital habitat for at least six endangered species and migrating birds on the Pacific flyway. Eco-tourists and environmental nonprofits seek restoration of the delta region through bi-national cooperative efforts. Nearby, the Cucapá people live in dwindling homelands and struggle to hang on to their way of life. The Colorado’s delta waters are as important to them as the blood in their veins.